Increasing Customer Satisfaction through Rural Tourism’s Quality Service, Experience, and Offered Value - Sukaris, Sukaris (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
Rural-based tourism is one of the potential contributors to the development of the rural economy. Therefore, an enhanced tourism value is critical to create visitor satisfaction during the trips. This study aims to empirically investigate tourist satisfaction by the rural tourism services quality and tourism experience, mediated by the offered value. This research analyzes 123 visitor responses, by constructing a Structural-Equation-Modeling with WarpPLS. The results of the research show that rural tourism service quality influences the customers’ value and satisfaction. The tailored experience enhances the offered value. Building a strong value proposal embedded in the tourism brings positive result to tourist’ satisfaction as well as mediate the effects of service quality and experience in it. The management should pursue a specified offered values that can be easily realized and accepted from the perspective of visitors.